1984
DOI: 10.1104/pp.76.4.1036
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison between Prolamellar Bodies and Prothylakoid Membranes of Etioplasts of Dark-Grown Wheat Concerning Lipid and Polypeptide Composition

Abstract: The aim of the present investigation was to find factors critical for the co-existence of prolamellar bodies and prothylakoids in etioplasts of wheat (Triticum aestivum L. cv Starke II). The lipid composition of the prolamellar body and prothylakoid fractions was qualitatively similar. However, the molar ratio of m ogalactosyl diacy4gycerol to digaactosyl diacylglycerol was higher in the prolamellar body fraction (1.6 ± 0.1), as was the lipid content on a protein basis. Protochlorophyllide was present in both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
60
2

Year Published

1988
1988
2008
2008

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 95 publications
(65 citation statements)
references
References 24 publications
3
60
2
Order By: Relevance
“…4 A and B), indicating that MGD1 is not important for plastid development in the dark. This result was somewhat unexpected because previous studies have shown that etioplast membranes contain high levels of MGD (29,30). One possible explanation is that the MGD synthase function of dark-grown Arabidopsis plants is fulfilled primarily by MGD2 and͞or MGD3, and not to any significant degree by MGD1.…”
Section: This Paper Describes the Identification And Characterizationcontrasting
confidence: 44%
“…4 A and B), indicating that MGD1 is not important for plastid development in the dark. This result was somewhat unexpected because previous studies have shown that etioplast membranes contain high levels of MGD (29,30). One possible explanation is that the MGD synthase function of dark-grown Arabidopsis plants is fulfilled primarily by MGD2 and͞or MGD3, and not to any significant degree by MGD1.…”
Section: This Paper Describes the Identification And Characterizationcontrasting
confidence: 44%
“…In yellow wild-type seedlings, lutein and violaxanthin are associated with the PLB seen in Figure 8A (Selstam and Sandelius, 1984). However, in the orange-yellow ccr2 seedlings, various lycopene and carotene isomers accumulate (Figure 2A), the PLB is absent ( Figures 8D and 8E), and unlike any previously described PLB-deficient plants (Sundqvist and Dahlin, 1997), POR levels are unaffected and Pchlide levels are reduced only slightly (Figure 9) (Axelsson et al, 1982;Sundqvist and Dahlin, 1997).…”
Section: Carotenoids Plb Formation and Photomorphogenesismentioning
confidence: 78%
“…The extremely fragile nature of an organelle which encloses starch granules causes a disruption of the envelope-membrane during isolation, thus precluding the isolation of the intact amyloplast while maintaining both its structural integrity and functional competence. Although the isolation of intact amyloplasts has been reported by several investigators using various plant materials (7,8,23,30), these reports appear to be still deficient; careful examination indicates that the evidence for the presence of an intact envelope surrounding the organelle appears to be rather weak.…”
mentioning
confidence: 93%